2022
DOI: 10.1002/rcm.9271
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric pressure matrix‐assisted laser desorption/ionization mass spectrometry of engine oil additive components

Abstract: The efficiency of lubricants strongly depends on the content of functional additives. In order to assess the chemical and structural changes taking place in the lubricating oil and its additives during operation, it is essential to develop a method for simple and prompt analysis.Methods: Two single additives as well as a fully formulated engine oil were analysed using an atmospheric pressure matrix-assisted laser desorption/ionization (AP-MALDI) source coupled to a linear trap quadrupole Orbitrap XL hybrid tan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 47 publications
0
1
0
Order By: Relevance
“…Further, this work revealed that AP MALDI is an efficient technique for directly determining lubricant additives from commercial oil products. 122 In 2023, Maurice and co-workers developed and optimized 48 well graphene nanoplatelets (GNP) doped AP MALDI target plates for the fast-screening analysis of additives in electronics and plastic consumer products, while a total of 56 additives including antioxidants, flame retardants, plasticizers, UV-stabilizers, and UV-filters were identified. 123 This helps in understanding the level of pollution in the environment and taking necessary measures to protect the environment and human health.…”
Section: Other Applicationsmentioning
confidence: 99%
“…Further, this work revealed that AP MALDI is an efficient technique for directly determining lubricant additives from commercial oil products. 122 In 2023, Maurice and co-workers developed and optimized 48 well graphene nanoplatelets (GNP) doped AP MALDI target plates for the fast-screening analysis of additives in electronics and plastic consumer products, while a total of 56 additives including antioxidants, flame retardants, plasticizers, UV-stabilizers, and UV-filters were identified. 123 This helps in understanding the level of pollution in the environment and taking necessary measures to protect the environment and human health.…”
Section: Other Applicationsmentioning
confidence: 99%
“…To separate the complex mixture of base oil components and additives, mass spectrometry is frequently combined with chromatographic techniques, such as gas chromatography (GC) [16,17] or liquid chromatography (LC) [18,19], which typically involves increased time and more elaborate sample preparation. For direct comprehensive chemical analysis of lubricants by MS, ambient ionization techniques such as desorption electrospray ionization (DESI) [20,21], matrix-assisted laser desorption ionization (MALDI) [22], direct analysis in real time (DART) [23], and atmospheric solids analysis probe (ASAP) [24] are becoming more widespread and popular. Instruments with high resolution and mass accuracy allow additives to be identified without complex sample preparation or the use of standards, as demonstrated by Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR MS) [25] or dielectric barrier discharge ionization mass spectrometry (DBDI-MS) [26].…”
Section: Introductionmentioning
confidence: 99%